Urinary KIM-1 Levels Normal Pregnancy vs Early-Onset Preeclampsia, and Late-Onset Preeclampsia - Morena, Sivia Heni; Vaulinne Basyir; Husna Yetti (Andalas Obstetrics And Gynecology Journal, 2025)
Introduction : Preeclampsia is a hypertensive disorder of pregnancy that contributes to high maternal mortality rates. Kidney Injury Molecule-1 (KIM-1) has been identified as a potential biomarker for detecting kidney injury and is suspected to play a role in the pathogenesis of preeclampsia. Objective : This study to determine the differences in urinary KIM-1 levels among normal pregnancies, early-onset preeclampsia, and late-onset preeclampsia at Dr. M. Djamil General Hospital, Padang. Methods : Cross-sectional comparative study included 72 pregnant women, consisting of 24 with normal pregnancies, 24 with early-onset preeclampsia, and 24 with late-onset preeclampsia. Urinary KIM-1 levels were measured using the ELISA method at the Biomedical Laboratory, Faculty of Medicine, Andalas University. Results : The mean urinary KIM-1 levels in the normal pregnancy group were 2.834 ± 0.957 ng/mL, in the early-onset preeclampsia group were 2.659 ± 1.175 ng/mL, and in the late-onset preeclampsia group were 2.694 ± 0.978 ng/mL. Statistical analysis showed no significant difference in urinary KIM-1 levels among the three groups (p > 0.05). Conclusion : There was no significant difference in urinary KIM-1 levels between normal pregnancies, early-onset preeclampsia, and late-onset preeclampsia. Further studies with larger sample sizes and more specific methods are needed to explore the potential of KIM-1 as a preeclampsia biomarker.